Anthropology in Indonesia : A Bibliographical Review - Koentjaraningrat, R.M., (Asian Studies - Book Archive pre-2000., 1975)
This book presents a review of the development and scope of anthropology in Indonesia. The first part of the book deals i.a. with the early writings of travellers and missionaries; the ethnological theories of G.A. Wilken; the accumulation of field data; theories on customs and social institutions; the study of adat law; studies of ancient social structure; studies of acculturation; studies after 1945; and the study and teaching of anthropology in present- day Indonesia. The second part of the book contains the bibliography and name and subject indexes.